The Importance of Developing Infographic Media Relics of The Hindu Buddha Kingdom at The Bumiayu Temple Site History Subject in SMK - Amalia, Ria; Susanti, LR. Retno; Raharjo, Makmum (Journal of Educational Sciences, 2025)
This research emphasizes the importance of developing infographic media to improve the teaching of Hindu-Buddhist heritage at Bumiayu Temple site in history subjects for vocational high schools (SMK). This research was conducted to address the lack of interesting and effective learning media in the conventional teaching method, which was deemed insufficient to increase students' understanding and interest in the subject. Using a needs analysis approach, data was collected through questionnaires distributed to teachers and students, focusing on competencies, learning styles, and student characteristics. Findings showed that 66.66% of students preferred a visual learning style, with most students showing moderate learning competence (60.77%). The infographic media proved to be a relevant solution, offering a visually appealing and accessible way to integrate historical content such as temple structures, cultural values, and related narratives. It also supports project-based learning by encouraging students' active participation and critical thinking. This study concludes that infographic media is a potential and strategic tool to improve the quality of history education in SMK. Future research could evaluate its implementation in classrooms to assess its direct impact on learning outcomes and its potential applicability to other history topics.